Combined de‐repression of chemoresistance associated mitogen‐activated protein kinase 14 and activating transcription factor 2 by loss of microrna‐622 in hepatocellular carcinoma - Fritz, Valerie; Malek, Lara; Gaza, Anne; Wormser, Laura; Appel, Majken; Kremer, Andreas; Thasler, Wolfgang E.; Neurath, Markus; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter; Siebler, Jürgen (Cancers, 2021)
Chemoresistance is a major hallmark driving the progression and poor prognosis of hepatocellular carcinoma (HCC). Limited chemoresponse of HCC was demonstrated to be mediated by mitogen‐activated protein kinase 14 (MAPK14) and activating transcription factor 2 (ATF2). Recently, we have demonstrated loss of control of RAS‐RAF‐ERK‐signaling as a consequence of miR‐622 downregulation in HCC. However, the majority of target genes of this potent tumorsuppressive microRNA had remained elusive. The MAPK14‐ATF2‐axis represents a collateral pathway ensuring persisting ERK‐activation in the presence of sorafenib‐mediated RAF-inhibition. In contrast to the function of the MAPK14‐ATF2‐axis, both the expression and regulation of MAPK14 and ATF2 in human HCC remained to be clarified. We found combined overexpression of MAPK14 and ATF2 in human HCC cells, tissues and in sorafenib resistant cell lines. High expression of MAPK14 and ATF2 was associated with reduced overall survival in HCC patients. Deciphering the molecular mechanism promoting combined upregulation of MAPK14 and ATF2 in HCC, we revealed that miR‐622 directly targets both genes, resulting in combined de‐repression of the MAPK14‐ATF2‐axis. Together, miR‐622 represents a superior regulator of both RAS‐RAF‐ERK as well as MAPK14‐ATF2‐signaling pathways in liver cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: HCC; Hepatocellular carcinoma; Liver cancer; MAPK14; MicroRNA; MiR‐622; RAS

Identification of novel targets of miR-622 in hepatocellular carcinoma reveals common regulation of cooperating genes and outlines the oncogenic role of zinc finger CCHC-type containing 11 - Gaza, Anne; Fritz, Valerie; Malek, Lara; Wormser, Laura; Treiber, Nora; Danner, Johannes; Kremer, Andreas E.; Thasler, Wolfgang E.; Siebler, Jürgen; Meister, Gunter; Neurath, Markus F.; Hellerbrand, Claus; et al. (Neoplasia, 2021)
The poor prognosis of advanced hepatocellular carcinoma (HCC) is driven by diverse features including dysregulated microRNAs inducing drug resistance and stemness. Lin-28 homolog A (LIN28A) and its partner zinc finger CCHC-type containing 11 (ZCCHC11) cooperate in binding, oligouridylation and subsequent degradation of tumorsuppressive let-7 precursor microRNAs. Functionally, activation of LIN28A was recently shown to promote stemness and chemoresistance in HCC. However, the expression and regulation of LIN28A in HCC had been unclear. Moreover, the expression, regulation and function of ZCCHC11 in liver cancer remained elusive. In contrast to "one-microRNA-one-target" interactions, we identified common binding sites for miR-622 in both LIN28A and ZCCHC11, suggesting miR-622 to function as a superior pathway regulator. Applying comprehensive microRNA database screening, human hepatocytes and HCC cell lines, patient-derived tissue samples as well as "The Cancer Genome Atlas" (TCGA) patient cohorts, we demonstrated that loss of tumorsuppressive miR-622 mediates derepression and overexpression of LIN28A in HCC. Moreover, the cooperator of LIN28A, ZCCHC11, was newly identified as a prognostic and therapeutic target of miR-622 in liver cancer. Together, identification of novel miR-622 target genes revealed common regulation of cooperating genes and outlines the previously unknown oncogenic role of ZCCHC11 in liver cancer.
CRIS-Team Scopus Importer:2021-05-07
Keywords: drug resistance; HCC; Hepatocellular carcinoma; microRNA; ZCCHC11

Palliative treatment of malignant intestinal obstruction with EUS-guided ileosigmoidostomy – a case report - Zundler, Sebastian; Wolff, Kerstin; Leppkes, Moritz; Gaza, Anne; Haberkamp, Sophie; Strobel, Deike; Siebler, Jürgen; Neurath, Markus; Waldner, Maximilian (Zeitschrift für Gastroenterologie, 2024)
We present the case of a 70-year-old patient of Caucasian origin under palliative chemotherapy for metastasized colorectal cancer, who presented with signs of complete small bowel obstruction six months after placement of a diverting ileostomy. Following previous tumor perforation, he was not considered a candidate for further surgical intervention. Thus, endoscopic ultrasound-guided enterocolostomy (i.e., ileosigmoidostomy) with a lumen-apposing metal stent was successfully performed in a coloenteric approach to restore the passage. Oral nutrition could be resumed the next day, and the patient could be discharged in substantially improved condition after three days.
CRIS-Team Scopus Importer:2024-12-13
Keywords: endoscopic ultrasound; endoscopy; oncology